2007
DOI: 10.1002/qj.71
|View full text |Cite
|
Sign up to set email alerts
|

On the boundary‐layer structure over highly complex terrain: Key findings from MAP

Abstract: Within MAP, one of the scientific projects was devoted to 'Boundary Layers in Complex Terrain'. In a number of subprojects, boundary-layer issues were addressed and detailed high-resolution multi-sensor observations were combined with simulation by models allowing for adequate parametrization of turbulence processes. In this contribution, the projects are briefly introduced and an attempt is made to summarize their key findings and to put them into a joint perspective. Spatial variability is found to be large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 65 publications
3
119
0
1
Order By: Relevance
“…In such topography, thermally driven winds may be generated at many different scales, with flow in the thin layer nearest to the ground responding to the local slope and local forcings and thicker flows responding to large-scale slopes and large-scale forcings [22,36]. Thermal and dynamical properties of flows at any scale influence flows on both larger and smaller scales [37]. Therefore, dynamic interactions between the slope and valley flows are typically observed on valley sidewalls [15].…”
Section: Slope/valley Wind Theorymentioning
confidence: 99%
“…In such topography, thermally driven winds may be generated at many different scales, with flow in the thin layer nearest to the ground responding to the local slope and local forcings and thicker flows responding to large-scale slopes and large-scale forcings [22,36]. Thermal and dynamical properties of flows at any scale influence flows on both larger and smaller scales [37]. Therefore, dynamic interactions between the slope and valley flows are typically observed on valley sidewalls [15].…”
Section: Slope/valley Wind Theorymentioning
confidence: 99%
“…The first studies that tested similarity scaling focused on flat and ideal terrain (e.g. Businger et al 1971), but recent work has shown that boundary-layer turbulence in a complex alpine valley still displayed reproducible and characteristic patterns that would allow the use of similarity theory (Rotach and Zardi 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, specific research projects have been organised more recently, including the 'MAP Riviera' project , under the comprehensive projects Mesoscale Alpine Programme (MAP; Bougeault et al, 2001;Bougeault and Binder, 2002), and Vertical Transport and MiXing (VTMX; Doran et al, 2002). In particular, within 'MAP Riviera' an intensive field experiment including both ground-based and airborne measurements was held in the target area of the Riviera Valley in ANALYSIS OF SECOND-ORDER MOMENTS 1751 the Swiss Alps, which opened the way to various innovative insights, summarised in Rotach and Zardi (2007) and Rotach et al (2008). The analysis of the huge amount of high-resolution turbulence data collected during the Special Observing Period (October-November 1999) and the combined numerical simulations have led to an improved vision of valley turbulence and its spatial structure, as documented in various papers based on the analysis of Riviera Valley data.…”
Section: Introductionmentioning
confidence: 99%